Genetic basis of alpha‐aminoadipic and alpha‐ketoadipic aciduria. Issue 5 (10th April 2015) - Hagen, Jacob; te Brinke, Heleen; Wanders, Ronald J. A.; Knegt, Alida C.; Oussoren, Esmee; Hoogeboom, A. Jeannette M.; Ruijter, George J. G.; Becker, Daniel; Schwab, Karl Otfried; Franke, Ingo; Duran, Marinus; Waterham, Hans R.; et al.
Abstract: Alpha‐aminoadipic and alpha‐ketoadipic aciduria is an autosomal recessive inborn error of lysine, hydroxylysine, and tryptophan degradation. To date, DHTKD1 mutations have been reported in two alpha‐aminoadipic and alpha‐ketoadipic aciduria patients. We have now sequenced DHTKD1 in nine patients diagnosed with alpha‐aminoadipic and alpha‐ketoadipic aciduria as well as one patient with isolated alpha‐aminoadipic aciduria, and identified causal mutations in eight. We report nine novel mutations, including three missense mutations, two nonsense mutations, two splice donor mutations, one duplication, and one deletion and insertion. Two missense mutations, one of which was reported before, were observed in the majority of cases. The clinical presentation of this group of patients was inhomogeneous. Our results confirm that alpha‐aminoadipic and alpha‐ketoadipic aciduria is caused by mutations in DHTKD1, and further establish that DHTKD1 encodes the E1 subunit of the alpha‐ketoadipic acid dehydrogenase complex.